Impact of Maternal Age on Singleton Birthweight in Frozen Embryo Transfer Cycles - Ni, Zhe-xin; Wan, Kun-ming; Zhou, Zhi-hao; Kuang, Yan-ping; Yu, Chao-qin (Frontiers in Endocrinology, 2022)
Background: Previous studies have investigated the effect of maternal age on assisted reproductive technology success rates. However, little is known about the relationship between maternal age and neonatal birthweight in frozen embryo transfer (FET) cycles. Whether maternal age influences singleton birthweight in FET cycles remains to be elucidated. Methods: This study was conducted at a tertiary care center, involving singleton live births born to women undergoing frozen–thawed embryo transfer during the period from January 2010 to December 2017. A total of 12,565 women who fulfilled the inclusion criteria were enrolled and grouped into four groups according to the maternal age: <30, 30–34, 35–39, and ≥40 years old. A multivariable linear regression analysis was conducted to reveal the relationship between maternal age and neonatal birthweight with controlling for a number of potential confounders. Results: The highest proportions of low birthweight (LBW, 4.1%), high birthweight (1.2%), preterm birth (PTB, 5.9%), and very PTB (0.9%) were found in the group over 40 years old, but no significant difference was observed among the four groups. Additionally, the 35–39-year-old group had the highest rate of very LBW (0.6%), whereas the 30–34-year-old group had the lowest rate of small for gestational age (SGA, 2.7%). However, multivariate analyses revealed that neonatal outcomes including PTB, LBW, and SGA were similar between the different maternal age groups. Conclusion: Grouping with different maternal age was not associated with mean birthweight and Z-scores of singletons resulting from FET.